Digital Inclusion and Citizenship Via Digital TV in Brazil - Americo, Marcos [UNESP]; Grossi de Carvaiho, Angela Maria [UNESP] (Univ Santiago Compostela, 2015)
The objective of this paper is to discuss issues related to digital inclusion and citizenship in Brazil, through the approach of public policies gestated by the State in an attempt to insert Brazil in the Information Society via Digital Television through two projects: Brazilian Digital TV System (SBTVD) and the Brazilian National Internet Broadband Plan (PNBL), also called Brazil Connected. The methodology used was exploratory, with the procedures of bibliographic and documentary research, with the goal of pointing out how actions have been articulating and gestated by the Brazilian government.
Keywords: Digital television; citizenship; digital inclusion; Brazilian digital television system; Brazilian national Internet broadband plan